The effect of rehabilitative exercises associated with the technique of Chiropractic in relieving the pain of muscle stretching in the lower back of people with a herniated disc - رؤى أكرم أكبر الحجازي أ.م.د عبير داخل حاتم السلمي (الرياضة المعاصرة)
The study aimed to prepare rehabilitative exercises associated with the technique of Chiropractic for herniated disc patients, and to identify the effect of rehabilitative exercises associated with the technique of Chiropractic in relieving muscle stretching pain in their lower back, and the experimental approach was adopted by designing the experimental and control groups on a sample of males between the ages of (30-45) years AD. Their number is (14) injured deliberately chosen from their community of origin by (70%) and they are among the injured who go to Al-Karkh General Hospital in Baghdad to receive treatment with a Chiropractic technique. One week for a period of (8) weeks for the period from (10/11/2019) until (2/1/2020),And after the end of the experiment, the two researchers verified the results of the study using the statistical bag system (SPSS-V26) to make the extracts and applications that the application of rehabilitative exercises associated with the technique of Chiropractic helped the injured in relieving the degree of pain from the two positions of bending the trunk in front and back, and outperforming their peers who received the technique of Chiropractic only. And that the application of rehabilitative exercises accompanying the technique of Chiropractic helps the sufferers to reduce the degree of pain from the position of bending the trunk, and to surpass them among their peers who have received the technique of Chiropractic only. According to the results of this study, it is necessary that the rehabilitation tools and means match the specificity of herniated disc sufferers, the type of rehabilitative exercise, and the possibility of providing it in hospitals, and that the need for it is necessary when rehabilitating the injured.